2021
DOI: 10.1093/eurpub/ckab164.077
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease and Adverse Pregnancy Outcomes: A Systematic Review and Meta-analysis

Abstract: Objective Chronic kidney disease (CKD) has been linked with adverse pregnancy outcomes, but few studies have examined the influence of cause and severity. The aim of this meta-analysis was to synthesize the evidence on CKD and adverse pregnancy outcome, by cause and severity of CKD where reported. Data sources We searched PubMed, Embase, and Web of Science from inception to May 2021. Study selection and Data Extraction: Studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
0
0
Order By: Relevance
“…First, previous studies have shown that CKD was associated with a higher risk of adverse pregnancy outcomes, 2 and this study yielded a similar conclusion with various categories of eGFR and proteinuria. Of note, in clinical practice, many women often consult about the effect of renal function on pregnancy outcomes, especially in women with abnormally elevated serum creatinine (SCr) or eGFR ,60 ml/min per 1.73 m 2 .…”
supporting
confidence: 84%
“…First, previous studies have shown that CKD was associated with a higher risk of adverse pregnancy outcomes, 2 and this study yielded a similar conclusion with various categories of eGFR and proteinuria. Of note, in clinical practice, many women often consult about the effect of renal function on pregnancy outcomes, especially in women with abnormally elevated serum creatinine (SCr) or eGFR ,60 ml/min per 1.73 m 2 .…”
supporting
confidence: 84%
“…El embarazo extrauterino es una condición adversa de la gestación donde el óvulo fertilizado se adhiere fuera de la cavidad uterina, comúnmente en una de las tubas uterinas (American College of Obstetricians and Gynecologists, 2021). Hay factores predisponentes como: bloqueo en las trompas de Falopio, endometriosis, infecciones de transmisión sexual, consumo de tabaco y antecedentes de intervención quirúrgica abdominal o pélvica (Mayo Clinic, 2021), antecedentes de cirugía tubárica previa, fertilización in vitro (Khalaf et al, 2021) mujeres mayores de 35 años, fumadoras (Huchon et al 2013). Los signos clínicos del embarazo extrauterino pueden ser diversos, pero habitualmente engloban dolor abdominal intenso y penetrante en un flanco del cuerpo, hemorragia vaginal atípica, vértigo, síncope, astenia y, en situaciones severas, choque (American College of Obstetricians and Gynecologists, 2021) (Khalaf et al, 2021).…”
Section: Introductionunclassified